EFEKTIVITAS AROMATERAPI LAVENDER TERHADAP PENINGKATAN LAMA TIDUR PADA IBU HAMIL TRIMESTER III - Ni Wayan Ari Adiputri; Catur Esty Pamungkas; Desi Rofita; Indriyani Makmun (JOMIS (Journal of Midwifery Science), 2023)
Sleep problems in pregnant women, especially in the third trimester will cause complications that can harm the mother and fetus. Giving aromatherapy is a safe alternative treatment for pregnant women, especially lavender aromatherapy. Lavender aromatherapy provides a calming and relaxing effect on tense nerves and muscles and this will help pregnant women to improve the quality and quantity of sleep. This study used a quasi-experimental design with a pretest posttest one group design method. Sampling used a non-probability sampling technique with consecutive sampling with a sample size of 30 third trimester primigravid mothers. The study was conducted in the City of Mataram from March to May 2022. The measurement of the quantity of sleep of pregnant women using the Sleep Diary Questionnaire, and statistical analysis techniques using the Wilcoxon test because the data distribution is not normally distributed. The purpose of this study was to determine the difference in the effectiveness of lavender aromatherapy on increasing sleep quantity in third trimester pregnant women. The results obtained that lavender aromatherapy was effective in increasing the quantity of sleep in third trimester pregnant women from an average of 6 hours to an average of 8 hours.